1996
DOI: 10.1016/0014-5793(95)01531-0
|View full text |Cite
|
Sign up to set email alerts
|

Topology of the secondary structure elements of ribosomal protein L7/L12 from E. coli in solution

Abstract: Topology of the secondary structure elements of ribosomal protein L7/L12 has been studied. The sequential assignment was obtained for main and side chain resonances. This allows the overall secondary structure to be described. The results of high resolution NMR studies show that dimer of the ribosomal protein L7/L12 from Escheriehia coli has a parallel (head-tohead) orientation of subunits, and N-terminal domain (NTD, residues Serl--Ser33) has no contacts with the C-terminal domain (CTD, residues Lys51-Lysl20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
1
3

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 22 publications
5
47
1
3
Order By: Relevance
“…An earlier study of Escherichia coli L12 by x-ray crystallography revealed the structure of the CTD to be comprised of three ␣ helices (␣4, ␣5, and ␣6) and a central three-stranded ␤ sheet (10). This structure was confirmed by a recent crystallographic study of L12 from Thermotoga maritima (30) and also by NMR analyses of E. coli L12 (16). More recently, the crystal structure of the complex between the N-terminal domain (helices ␣1 and ␣2) of L12 and L10 from T. maritima was elucidated using a reconstituted sample (6).…”
supporting
confidence: 56%
See 1 more Smart Citation
“…An earlier study of Escherichia coli L12 by x-ray crystallography revealed the structure of the CTD to be comprised of three ␣ helices (␣4, ␣5, and ␣6) and a central three-stranded ␤ sheet (10). This structure was confirmed by a recent crystallographic study of L12 from Thermotoga maritima (30) and also by NMR analyses of E. coli L12 (16). More recently, the crystal structure of the complex between the N-terminal domain (helices ␣1 and ␣2) of L12 and L10 from T. maritima was elucidated using a reconstituted sample (6).…”
supporting
confidence: 56%
“…7) and its binding to L10 (for review see Ref. 8), the globular C-terminal domain (CTD) (9,10), which interacts with the elongation factors (11)(12)(13)(14), and a hinge region, which connects the two domains (15,16). It was generally accepted that, in the bacterial ribosomal large subunit, two L12 dimers bind to L10 to form a pentameric complex, L10⅐(L12) 2 ⅐(L12) 2 (7,17).…”
mentioning
confidence: 99%
“…NMR studies of L7/L12 in solution predicted that dimers of the ribosomal protein L7/L12 from Escherichia coli had a parallel (head-to-head) orientation and that the N-terminal domain had no contacts with the C-terminal domain. The hinge region was predicted as an unordered structure (Bocharov et al, 1996). However, the 3D high resolution structure of L7/L12 as a dimer linked to two proteolysed fragments confirmed the existence of the three predicted domains but revealed a totally different organisation ( Fig.…”
Section: Prokaryotic Equivalents Of the P-proteinsmentioning
confidence: 92%
“…1C); by contrast, the crosspeaks from the 50S subunit are typical of those of a highly structured protein. Examination of the HSQC spectra in more detail indicates that the large majority of the observable resonances from the 50S correspond to those reported for the interdomain hinge and the CTD (residues 43-120) of free L7͞L12 (11) (Fig. 1B).…”
Section: Hsqcmentioning
confidence: 98%
“…1 H NMR spectroscopy on isolated 50S and 70S ribosomes has provided evidence for regions of local motional averaging, revealing several narrow resonances that have been attributed to L7͞L12 (9,10). 15 N NMR spectroscopy of isolated L7͞L12 proteins shows two apparently independent structured domains linked by a flexible hinge, with the nuclear Overhauser effect patterns indicating an N-terminal domain (NTD) dimer independent of the respective C-terminal domain (CTD) (11). Similar studies of a pentameric complex (the four copies of L7͞L12 along with L10) show that the binding of L10 to the NTD of L7͞L12 causes the disappearance of the resonances of the latter (12).…”
mentioning
confidence: 99%